Islam and democracy - Esposito, John L. (Oxford University Press, 1996)
"Are Islam and democracy on a collision course? Do Islamic movements seek to "hijack democracy"? How have governments in the Muslim world responded to the many challenges of Islam and democracy today?" "A global religious resurgence and calls for greater political participation have been major forces in the post-Cold War period. Across the Muslim world, governments and Islamic movements grapple with issues of democratization and civil society. Islam and Democracy explores the Islamic sources (beliefs and institutions) relevant to the current debate over greater political participation and democratization." "Esposito and Voll use six case studies - Algeria, Egypt, Iran, Malaysia, Pakistan, and Sudan - to look at the diversity of Muslim experiences and experiments. At one end of the spectrum, Iran and Sudan represent two cases of militant, revolutionary Islam establishing political systems. In Pakistan and Malaysia, however, the new movements have been recognized and made part of the political process. Egypt and Algeria reveal the coexistence of both extremist and moderate Islamic activism and demonstrate the complex challenges confronting ruling elites. These case studies prove that despite commonalities, differing national contexts and identities give rise to a multiplicity of agendas and strategies."--Jacket